TINGKAT KEBUGARAN JASMANI PADA PENDERITA TUBERKULOSIS PARU DI PUSKESMAS RAWAT JALAN SIDOMULYO PEKANBARU - Ricky Imran (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Tuberculosis (TB) is an infectious disease caused by the bacillus Mycobacterium tuberculosis that infected among 20-43% worldwide pupulation. TB still a major health problem in the world. According to World Health Organization (WHO) there are 0,4-0,5 million patients in Indonesia. This was a descriptive observasional study to know body fitness of lung TB in Sidomulyo Outpatient Community Health Center, Pekanbaru using Harvard Step Test method. The data from the 33 patients were taken from the interview and Harvard Step Test in Sidomulyo Outpatient Community Health Center, Pekanbaru on June 2014. The result of this study indicated that 96,97% of lung TB patients whom being treated in the were have very low physical fitness. About 66,67% were male patients and 33,33% were female patients. 27,27% patients were 25-29 years old age group. In job classification were found 48,49% with mid classified jobs. By using Brinkman Index patients with medium and heavy smoking history 24.24% each, the most duration of treatment were found 75,75% in advanced phase, and 93,94% patient are orderly treated.Keywords: Tuberculosis, Harvard Step Test, Phisycal Fitness